Keterampilan Menulis Surat Pribadi Bahasa Jerman - Waru, Nursyahbani Tenri; Dalle, Ambo (Interference: Journal of Language, Literature, and Linguistics, 2021)
This research is a descriptive quantitative research which aims to determine the skill level of students' personal letter writing. The sample of this research is the 12th grade students of SMA Negeri 1 Watansoppeng is 20 students and the sample is total sampling. The data in this research were students of class XII Language SMA Negeri 1 Watansoppeng. The research data were obtained through a personal letter writing skill test and the data were analyzed using the percentage technique. The result of this research that the students' personal letter writing skills is in the sufficient category (71.45%) and the results of the questionnaire analysis show at percentage of  18 students (90%) like to write German and it is also supported by external factors where 19 students (95%)stated that the teacher always provides gives excerise about German writing skills while the inhibiting factor in students' personal letter writing skills comes from internal factors which is 14 students (70%) struggling in composing German sentences.